Impact of lower limb movement on the hemodynamics of femoropopliteal arteries: A computational study. (July 2020) - Colombo, Monika; Luraghi, Giulia; Cestariolo, Ludovica; Ravasi, Maddalena; Airoldi, Anna; Chiastra, Claudio; Pennati, Giancarlo
Highlights: Study of the effect of walking, knee flexion and hip rotation on local hemodynamics. Moving-boundary CFD simulations of an idealized femoropopliteal artery (FPA). The leg movement has a relevant impact on the FPA hemodynamics. Walking speed and inlet flow-rate have maximum impact on FPA hemodynamics. Abstract: Femoropopliteal arteries (FPAs) are subjected to a wide range of deformations, mainly determined by leg movement. FPAs are often affected by atherosclerotic plaque development, presumably influenced by the biomechanics of surrounding tissues. Although abnormal hemodynamics in FPAs appears to be an important factor in driving plaque development, to date it has been investigated in few studies, in which the leg was modeled in either fixed straight or bent configuration. Hence, the current work investigates the impact of leg movement on FPA hemodynamics. An idealized model of FPA was created to perform moving-boundary computational fluid dynamics analyses. By mimicking hip rotation, knee flexion and complete movement of walking, the hemodynamics was compared between moving- and fixed-boundary models. Moreover, additional features affecting the hemodynamics (e.g. flow-rate curve amplitude, walking speed) were examined. Significant hemodynamic differences were found between the moving- and fixed-boundary models, with the leg movement inducing higher time-averaged wall shear stress (TAWSS) (up to 66%). The flow-rate amplitude and walking period were the most influential parameters (differences in TAWSS up to 68% and 74%, respectively). In conclusion, this numerical approach highlighted the importance of considering leg movement to investigate FPA hemodynamics, and it could be employed in future patient-specific analyses.